The Impact of Oncogenic Viruses on Cancer Development: A Narrative Review - Maria Karoliny da Silva Torres; Gabriel dos Santos Pereira Neto; Izaura Maria Vieira Cayres Vallinoto; Leonardo Oliveira Reis; Antonio Carlos Rosário Vallinoto (Biology)
Oncogenic viruses are infectious agents that can cause cancer in humans and animals. They are estimated to be responsible for approximately 12% of human cancers worldwide. These viruses trigger a series of mechanisms that allow them to insert their genetic material into host cells, disrupting normal cellular processes and leading to uncontrolled growth and tumor formation. This article reviews the literature on the main oncogenic viruses and reports on newly identified viruses potentially associated with cancer development, addressing the mechanisms of oncogenesis and the types of cancers associated. In addition, the article brings together the evidence for preventive strategies, such as vaccination, and therapeutic advances in combating oncogenic viral infections. This review discusses the role of early detection and treatment in managing virus-related cancers globally. This article reviews current prevention and treatment strategies, including HPV and HBV vaccines and antiviral therapies, and mentions future approaches like immunotherapies and CRISPR/Cas9. Therefore, this article underscores the importance of studying the dynamics of co-infection and the role of human microbiota in viral persistence and carcinogenesis, which opens new possibilities for combination therapies and microbiome-based interventions to slow the progression of viral-related tumors.